Contribution of haplotypes across the fibrinogen gene cluster to variation in risk of myocardial infarction - Mannila, Maria Nastase; Eriksson, Per; Lundman, Pia; Samnegård, Ann; Boquist, Susanna; Ericsson, Carl-Göran; Tornvall, Per; Hamsten, Anders; Silveira, Angela (Thrombosis and Haemostasis, 2005)
Fibrinogen has consistently been recognized as an independent predictor of myocardial infarction (MI). Multiple mechanisms link fibrinogen to MI; therefore disentangling the factors underlying variation in plasma fibrinogen concentration is essential. Candidate regions in the fibrinogen gamma (FGG), alpha (FGA) and beta (FGB) genes were screened for single nucleotide polymorphisms (SNPs). Several novel SNPs were detected in the FGG and FGA genes in addition to the previously known SNPs in the fibrinogen genes. Tight linkage disequilibrium extending over various physical distances was observed between most SNPs. Consequently, eight SNPs were chosen and determined in 377 postinfarction patients and 387 healthy individuals. None of the SNPs were associated with plasma fibrinogen concentration or MI. Haplotype analyses revealed a consistent pattern of hap-lotypes associated with variation in risk of MI. Of the four haplo-types inferred using the FGA –58G> A and FGG 1299+79T> C SNPs, the most frequent haplotype, FGG-FGA*1 (prevalence 46.6%), was associated with increased risk of MI (OR 1.51; 95%CI 1.18, 1.93), whereas the least frequent haplotype, FGGFGA*4 (11.8%), was associated with lower risk of MI (OR 0.79 95%CI 0.64, 0.98). In conclusion, fibrinogen haplotypes, but not SNPs in isolation, are associated with variation in risk of MI.
Keywords: Fibrinogen gene cluster; myocardial infarction; SNPs; haplotypes